(untitled) (The Pakistan Development Review, 1965)
The emergence of stable and quasi-stable population theory has been one of the most interesting developments of demographic theory in the recent past. Zelnik and Rahman Khan writing in the Spring 1965 issue of this Review have applied this methodology to Pakistani data with rather interesting resultsJ. The purpose of this present note is two-fold. First, is to discuss the assumptions and procedures of the Zelnik-Rahman Khan use of the quasi-stable model. In other words, accepting the validity of the model and also its applicability to Pakistan, have the authors made good use of it? Second, and more basically, is the quasistable methodology in fact relevant for Pakistan, given the data available? Let us begin with a brief review of the stable and quasi-stable population models as they have developed in the last ten years.